2011
DOI: 10.6106/kjcem.2011.12.6.120
|View full text |Cite
|
Sign up to set email alerts
|

An Algorithm for Hoisting Time Calculation in Super-tall Building Construction

Abstract: An installation of the construction lift has a few limitations by many constrains and these have influences on labor productivity, that can be changed by vertical-transportation management. In the super-tall building construction, a management of construction lift operation is one of the most important factor, but existing methodologies depend on skilled practitioners' experiences. And it is true that the expertise resulted by the experiences does not transfer to the next generation. This study is a part of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Although there are differences in each company and in each region, the TACT technique is most commonly used for finishing work management for high-rise building construction [2]. The TACT technique is a finishing work process management method for sub-dividing work into each floor and process, distributing human resources and equipment into even periods of each construction time, adjusting the preceding and lagging relationship of works on the same floor, and planning for the sequential operation of the work on each floor.…”
Section: Finishing Work Schedule Management For High-rise Constructionmentioning
confidence: 99%
“…Although there are differences in each company and in each region, the TACT technique is most commonly used for finishing work management for high-rise building construction [2]. The TACT technique is a finishing work process management method for sub-dividing work into each floor and process, distributing human resources and equipment into even periods of each construction time, adjusting the preceding and lagging relationship of works on the same floor, and planning for the sequential operation of the work on each floor.…”
Section: Finishing Work Schedule Management For High-rise Constructionmentioning
confidence: 99%
“…For a more accurate estimation of the hoisting time, this study adopted calculation method considering acceleration and deceleration, suggested by Cho et al [12]. Also, we utilized the acceleration and deceleration time of single-cage lift which was provided by Cho et al [13]. And we identified the acceleration and deceleration time of double-cage lift by interviewing with the hoist manufacturer who is developed the double-cage lift.…”
Section: Calculation Methods Of Hoisting Timementioning
confidence: 99%
“…Cho et al conducted a study on construction lift operation planning in terms of lifting height and loading (Cho, 2011). Further, Shin proposed optimal operation of temporary construction lifts in a super high-rise building based on simulation and genetic algorithm.…”
Section: Research Trendmentioning
confidence: 99%